2020
DOI: 10.3390/antibiotics9040204
|View full text |Cite
|
Sign up to set email alerts
|

Development of Antimicrobial Stewardship Programmes in Low and Middle-Income Countries: A Mixed-Methods Study in Nigerian Hospitals

Abstract: Antimicrobial resistance (AMR) is a major concern facing global health today, with the greatest impact in developing countries where the burden of infectious diseases is much higher. The inappropriate prescribing and use of antibiotics are contributory factors to increasing antibiotic resistance. Antimicrobial stewardship programmes (AMS) are implemented to optimise use and promote behavioural change in the use of antimicrobials. AMS programmes have been widely employed and proven to improve antibiotic use in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 25 publications
2
28
0
Order By: Relevance
“…Though AMS programs have proven to improve antibiotic use in developed countries, AMS strategies to contain AMR are unsuccessfully executed in developing countries 56 which has led to an urgency to establish, implement and evaluate effective AMS programs 57–59 in these territories. To tackle this emergency, in 2016, the WHO and the United Nations General Assembly ratified the implementation of AMS programs globally and at the institutional-level.…”
Section: History Of Amsmentioning
confidence: 99%
“…Though AMS programs have proven to improve antibiotic use in developed countries, AMS strategies to contain AMR are unsuccessfully executed in developing countries 56 which has led to an urgency to establish, implement and evaluate effective AMS programs 57–59 in these territories. To tackle this emergency, in 2016, the WHO and the United Nations General Assembly ratified the implementation of AMS programs globally and at the institutional-level.…”
Section: History Of Amsmentioning
confidence: 99%
“…The inappropriate use of antimicrobial drugs has become one of the main causes of increased AMDR worldwide [2]. Therefore, current strategies to combat AMDR are primarily focused on antimicrobial stewardship [3][4][5]. Moreover, according to the One Health perspective, AMDR can occur for different reasons, including human, animal or environmental factors [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…An Australian study by Hardefeldt et al (2018a) also reported that cost was as an important factor in the decision regarding antimicrobial prescription indicating that cost of the antimicrobial is an important consideration regardless of the geographical location. However, the cost and affordability of medications is especially important in low-income settings where prescribers often choose cheaper alternatives ( Kpokiri, Taylor & Smith, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore evident that there is a need to educate veterinarians on the importance of use of antibiogram before making antibacterial treatment decisions. However, it is worth pointing out that in low- and middle-income countries (LMIC) there is usually lack of laboratories to perform the necessary tests and access is an important limiting factor ( Petti et al, 2006 ; Kpokiri, Taylor & Smith, 2020 ). Therefore, improvement of access to laboratory facilities in such situations would play an important role in the fight against AMR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation